Analisis Dampak Penerapan Sistem Enterprise Resource Planning (ERP) Terhadap Kinerja Pengguna Pada Perusahaan Manufaktur Di Manado - Supranata, Mardani; Lailiyah, Nadhifatul (Jurnal Akuntansi Manajerial, 2025)
The following study aims to find out how the application of ERP impacts the performance of manufacturing company users in Manado in 2024 and various factors that have an impact on the success of ERP applications so that ERP can help users. The purpose of the following study is to evaluate how the implementation of ERP systems in manufacturing companies in Manado has a positive impact on user performance. Perceived system complexity, perceived system suitability, user trust in the organisation's infrastructure, perceived system usability and convenience and factory performance are the variables used to assess how ERP system implementation affects user performance. The following study uses a qualitative methodology that is descriptive, analytical, and evaluative in nature. This study shows that the use of ERP systems can improve user performance.